Sperm characteristics in a sample of healthy adolescents in São Paulo, Brazil - Mori Marcos Mitsuyoshi; Cedenho Agnaldo Pereira; Koifman Sergio; Srougi Miguel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The article presents preliminary data from a prospective investigation in a sample of healthy 14-17-year-old students from a technical school in Sao Paulo, Brazil. Ninety-six Tanner stage 5 and thirty-one Tanner stage 4 adolescents were evaluated: testicular volume was measured using a Prader orchidometer, and semen analysis was performed according to standard procedures. Median testicular volume was 20.0ml among Tanner 5 students and 15.0ml in Tanner 4 students in both the right and left testes. No significant differences were found in sperm volume or motility. Median concentration was 66.0 million/ml for Tanner 5 and 47.0 million/ml for Tanner 4 subjects. Morphological patterns showed abnormal forms in 81.9% of Tanner 5 and 93.6% of Tanner 4 adolescents. Oligospermia (sperm concentration < 5 million/ml) was observed in 7.3% of Tanner stage 5 and 12.9% of Tanner stage 4 individuals. Azoospermia was observed in 3 students (1.8%), with counts less than 1.0 in 8 students (4.8%). The authors discuss the observed results, analyzing the potential implications arising from biological development and potential environmental exposures.